The Bridge Kingdom - Jensen, Danielle L. (Jensen, Danielle L. Bridge kingdom series, 2024)
"The iconic Bridge Kingdom series begins: a sweeping, sizzling fantasy romance filled with political intrigue and passionate love, from the New York Times bestselling author of A Fate Inked in Blood"--